2017
DOI: 10.1017/jfm.2017.288
|View full text |Cite
|
Sign up to set email alerts
|

Injection into boundary layers: solutions beyond the classical form

Abstract: This theoretical and numerical study presents three-dimensional boundary-layer solutions for laminar incompressible flow adjacent to a semi-infinite flat plate, subject to a uniform free-stream speed and injection through the plate surface. The novelty in this case arises from a fully three-dimensional formulation, which also allows for slot injection over a spanwise lengthscale comparable to the boundary-layer thickness. This approach retains viscous effects in both the spanwise and transverse directions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The injection through the plate surface is concentrated in the region |ζ | < ζ 0 as defined by (8) and indicated by the arrows, whilst ζ = 0 is a symmetry line. For β = 0 (a, c, e) three distinct flow regimes are observed as described in [14]. However results for β = 0.1 (b, d, f) show a qualitatively different response (e) K > K I I , a much more prominent low-speed streak is observed which is separated from the outer flow by a semi-circular free shear layer.…”
Section: Results: Three-dimensional Injection Statesmentioning
confidence: 87%
See 4 more Smart Citations
“…The injection through the plate surface is concentrated in the region |ζ | < ζ 0 as defined by (8) and indicated by the arrows, whilst ζ = 0 is a symmetry line. For β = 0 (a, c, e) three distinct flow regimes are observed as described in [14]. However results for β = 0.1 (b, d, f) show a qualitatively different response (e) K > K I I , a much more prominent low-speed streak is observed which is separated from the outer flow by a semi-circular free shear layer.…”
Section: Results: Three-dimensional Injection Statesmentioning
confidence: 87%
“…The previous work of [14] showed that for K > 0 (injection) and no applied pressure gradient (β = 0), three distinct flow regimes are observed, as the injection-slot width ζ 0 is increased. These three regimes are delineated by the injection rates: 0 < K < K I ≈ 0.876, K I < K < K I I ≈ 1.95 and K > K I I .…”
Section: Results: Three-dimensional Injection Statesmentioning
confidence: 98%
See 3 more Smart Citations